Address Term Used By The Instagram Users - Egi Agung Andikha; Ambalegin Ambalegin (LPPM Universitas Bumigora Mataram, 2022)
The purpose of this research was to analyze the kinds of address terms in media social, especially on Instagram. The researchers used one of David Beckham’s posts as the object of research. This research used (Wardhaugh, 2006) and (Chaika, 1982) theories about kinds of address terms. The researchers used the descriptive qualitative method. The result of this research shows that from seven types of Wardhaugh and Chaika theories, the researchers found seven kinds of address terms that are used by Instagram users on David Beckham’s posts. They were First Name (FN), Last Name (LN), Title (T), Title plus Last Name (TLN), Special Nicknames (SN), Pet Names (PN), and Kindship Terms (KT). The most commonly used by Instagram users is First Name (FN) there were five data, three data in Last Name (LN), two data in Pet Name (PN), two data in Kindship Terms (KT), one data in Title (T), one data in Title plus Last Name (TLN), and one data in Special Nicknames (SN). Keywords: address term, media social, instagram, type